2019
DOI: 10.1186/s12913-019-4451-0
|View full text |Cite
|
Sign up to set email alerts
|

What has driven the spatial spillover of China’s out-of-pocket payments?

Abstract: Background Even though China launched a series of measures to alleviate several financial burdens (including health insurance scheme, increased government investment, and so on), the economic burden of health expenditure has still not been alleviated. Out-of-pocket payments (OPPs) show not only a time correlation but also some degree of spatial correlation. The aims of the current study were thus to identify the spatial cluster of OPPs, to investigate the main factors affecting variation, and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…It is found that spatial interaction or spatial dependence are present in health expenditure across regions in China, which is consistent with US state-level studies [40], and some studies on government health expenditure, health insurance financing or OOP spillover effect in China [41][42][43][44][45]. In combination with the spatial effect, various factors have different influence mechanisms on health expenditure growth.…”
Section: Health Expenditure Growth Has a Significant Space Spillover supporting
confidence: 80%
“…It is found that spatial interaction or spatial dependence are present in health expenditure across regions in China, which is consistent with US state-level studies [40], and some studies on government health expenditure, health insurance financing or OOP spillover effect in China [41][42][43][44][45]. In combination with the spatial effect, various factors have different influence mechanisms on health expenditure growth.…”
Section: Health Expenditure Growth Has a Significant Space Spillover supporting
confidence: 80%
“…However, this is still a contended issue. In a spatial model study by Zhang et al (2019), the number of hospital beds was found to increase the co-payment component, directly or indirectly, while Yang et al's (2021), based on the fixed effects model, showed that the effect of increasing the number of hospital beds in the district and district units decreased co-payment. Considering that the results of these preceding studies differed, follow-up studies at the individual and regional levels are needed for an accurate interpretation.…”
Section: Discussionmentioning
confidence: 95%
“…Through a spatial panel analysis of 48 states in the United States, Bose (2014) suggests that the higher the proportion of older adults in the population, the higher the per capita medical expenditure. Zhang et al (2019), using geographic information systems (GIS) analysis of a panel of data from 31 regions in China, argue that ageing of the population is, directly and indirectly, significantly related to the out-of-pocket expenditure, and Łyszczarz et al (2021), based on the association between socioeconomic factors and out-of-pocket expenditures in 16 Polish regions, found that the out-of-pocket expenditure increased by 8.5%when the proportion of the elderly in the total population increased by 1%. It is thus evident that the burden of co-payments increases when the population ages, suggesting that it is difficult to manage excessive medical expenses with the current health insurance system alone.…”
Section: Discussionmentioning
confidence: 99%